Differences in a space of equals: gender relations in a Rural Teachers College (1950-1960) (2016)
In this study, we examine the topic of a rural boarding school based on the narratives of subjects who had an instructional experience in an educational public institution in the city of Osório/ RS, Brazil, during a rural teachers training project.The subject and the objective of this research fall in the field of History of Education, and the development of gender relations in a coeducational school in the first half of the XX century.This study assumes memory as a document and oral history as methodology.The school represented to these youth the possibility of getting to know a world different   from   their    familiar    culture. It also promoted the dissemination of knowledge and enabled socialization. Plurality, co-education, and harmonious living seem to encapsulate the memories of this institution in Osório as an extraordinary school, a unique experience in the life of those students and teachers. This article discusses the ease of access to rural teacher training by young men who had the guarantee of a permanent situation at school as boarders. This benefit may explain why the profession of rural teacher was sought to a greater extent by men rather than women.